The Impact of Surface Voltage on Photoluminescence Response for the Detection of Copper and Iron Contamination in Silicon. Issue 9 (31st October 2021) - Nassiet, Thomas; Duru, Romain; Le-Cunff, Delphine; Bremond, Georges; Bluet, Jean-Marie
Abstract : Herein, silicon substrates intentionally contaminated by iron and copper are analyzed by an innovative technique based on photoluminescence (PL) measurement, with the aim to evaluate the sensitivity of this technique to low level contamination and its capability for further in‐line monitoring during devices fabrication. Measurements are carried out directly after samples preparation, with the combined use of PL and corona discharges to separate the contribution of metallic contamination from interface properties on the PL signal. The sensitivity of PL to both iron and copper contamination in silicon with higher sensitivity when surface recombination is minimized is shown. Therefore, this work highlights the importance of surface properties monitoring for the optimization of PL detection of metallic contamination. Abstract : Bias dependent photoluminescence (PL) is explored as a high sensitivity technique to characterize iron and copper contamination diffused in crystalline silicon. Herein, a strong increase in metallic contamination sensitivity with PL measurement by the minimization of surface recombination processes with enhanced field effect passivation using corona charges is shown.